Women leadership model in Islamic Religious College (PTKIN) in implementing gender responsive program policies (Gender studies at IAIN Bukittinggi, IAIN Ponorogo, and IAIN Metro Lampung) - Meria, Aziza; Hakim, Lukmanul; Hasnah, Radhiatul; Nursa, Ruri Afria; Hadi, Rahmad Tri (Universitas Islam Negeri Ar-Raniry, 2022)
This research is a disparity in women's leadership, especially in the context of Islamic universities in Indonesia. This is because women's leadership still faces many challenges, such as stereotyping and marginalisation of women, both in the educational, social and cultural spheres. This study aims to analyse and evaluate the leadership model of the female rector of PTKIN in implementing gender-responsive programs. This research is field research, namely field research using a qualitative approach. The data needed is the PTKIN rector model including the rector of IAIN Bukittinggi, IAIN Ponorogo, and IAIN Metro Lampung. Data collection techniques using observation, interviews and documentation, with descriptive and narrative analysis. The results of the study indicate that in implementing gender-responsive programs, namely planning and implementing activities, it shows that the three rectors of PTKIN, namely IAIN Bukittinggi, Ponorogo, and Metro Lampung, tend to be transformational-democratic. It is proven from the seven prerequisites that have been set that the planning of gender-responsive programs in its planning is moderate and open in accepting input, proposals and suggestions regarding the planning and implementation of activities as well as budgeting for activities from their subordinates. At the time of performance, they facilitated the administrative process, budget disbursement, and bureaucracy. While in the evaluation activities, although they are still said to be democratic and moderate, in the evaluation activities their leadership style is also a little permissive, an indication that they accept the evaluations carried out.